CCC_implementing the construction control room on a fast-paced project: the case study of the Beirut port explosion. Issue 5 (4th April 2023) - Ezzeddine, Ali; Shehab, Lynn; Srour, Issam; Power, William; Zankoul, Emile; Freiha, Elie
Abstract: The world is a dynamic and ever-changing environment leading decision makers to believe that from plan to execution, unforeseen conditions will undoubtedly occur. The military is known to face unforeseen obstacles while conducting the operations forcing leaders to plan for deviations. The construction sector is not far from the military in terms of planning and executing under uncertainty. Military control rooms has shown their effectiveness in several industries, but little research has been made on the use of control rooms in construction. This paper illustrates how a control room could be used in construction and highlights the associated advantages. Thus, the objective of this research is to study the deployment of a Construction Control Room (CCR) for project monitoring and control on a live project where intense collaboration is required. Results of this study show the effectiveness of using a CCR for project monitoring and control, and how it could be rapidly deployed for crisis management using digital tools.